A Comparison 24 Hour Intraocular Pressures Between Travoprost 0.004% and Timolol Gel 0.1% on Controlled Primary Open Angle Glaucoma - Puranto Budi Susetyo; Virna Dwi Oktariana; Edi Supiandi; Joedo Prihartono (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: To compare 24 hours intraocular pressure (IOP) in patients controlled primary open angle glaucoma treated with timolol gel 0.1% versus travoprost 0.004%. Method: 26 controlled primary open angle glaucoma patients were randomized to received travoprost 0.004% dosed in the evening or timolol gel 0.1% dosed in the morning. After 4 weeks of treatments 24 hours IOP curved was performed at 9 a.m until 6 a.m every 3 hours. Result: The mean IOP of travoprost 0.004% group was 12.2±1.5 mmHg and timolol 0.1% group was 13.4±1.9 mmHg (p>0.05). The IOP fluctuation of travoprost 0.004% was 3.9±1.4 mmHg and timolol gel 0.1% was 5.9±1.4 mmHg (p<0.05). Peak IOP travoprost 0.004% was 14.3±1.7 mmHg and timolol gel 0.1 % was 16.8±1.7 mmHg (p<0.05). Travoprost 0.004% has lower IOP in almost each point measurement compare to timolol gel 0.1%. Conclusion: Travoprost 0.004% has lower fluctuation, peak and mean IOP compare to timolol gel 0.1%. Keywords: Primary open angle glaucoma, IOP fluctuation, peak IOP, travoprost 0.004%, timolol gel 0.1%